THEORETICAL FOUNDATIONS OF UNIVERSAL DESIGN FOR LEARNING, SUPPORT IN PEDAGOGICAL PRACTICE - Claudia Patricia Moncada Buitrago (DIALÉCTICA, 2025)
To advance inclusive education, it is important to identify the theoretical foundations of universal design for learning, as a support in pedagogical practice, highlighting that alternative for transformation and recognition of the needs of students or barriers that teachers have ay the time of pedagogical planning, where reasonable adjustments are implemented taking into account the tools, styles, ways of learning. In order to understand and interpret how universal design allows the teacher to create spaces that strengthen the processes I pedagogical practice. A review of the literature will be carried out that theoretically supports the universal design for learning as a support in the teaching work that is developed before, during and after each moment of planning, this is developed before, during and after each moment of planning, this theoretical review allows contextualizing the three elementary principles and guidelines that are relevant for the strengthening of educational praxis that emphasizes teaching and learning, at the same time, take into account the three networks that are known for neuroscientific foundations. The methodology is based on a qualitative, interpretative approach, with a theoretical documentary review technique that is focused on the framework of universal design between the historical and the current. It is concluded that universal design is important for learning in the process of executing the plans designed by the teacher to interact with the learning that the student must acquire, demonstrating the different ways of reaching knowledge, affectivity and strategy.